2022
DOI: 10.1155/2022/2005935
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Home Remedies for Orofacial Pain during the Coronavirus Disease 2019 Pandemic: Their Value and Limitations

Abstract: Background. The coronavirus disease 2019 (COVID-19) pandemic has impeded access to timely dental care, and there is an urgent need for adjuvant therapies that can reduce orofacial pain in emergencies. Aims. To provide information on the benefits and limitations of eight representative home remedies as palliative care for orofacial pain during the coronavirus disease 2019 (COVID-19) pandemic. Methods. PubMed and Medline were electronically searched for eight home remedies for orofacial pain that can be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
3
0
1
Order By: Relevance
“…As previous studies reported, the psychological distress evaluated by CPDI was observed in some chronic diseases, including asthma, cancer, psychiatric disorders and autoimmune arthritis, that patients suffered from illness itself and the limitation of access to primary care [22,23]. Thus, nonpharmacologic therapy and TMJ home nursing guidance are necessary for patients who suffer from TMJ pain and are quarantined at home [24].…”
Section: Discussionmentioning
confidence: 98%
“…As previous studies reported, the psychological distress evaluated by CPDI was observed in some chronic diseases, including asthma, cancer, psychiatric disorders and autoimmune arthritis, that patients suffered from illness itself and the limitation of access to primary care [22,23]. Thus, nonpharmacologic therapy and TMJ home nursing guidance are necessary for patients who suffer from TMJ pain and are quarantined at home [24].…”
Section: Discussionmentioning
confidence: 98%
“…Использование натуральных продуктов при орофациальной боли имеет значительный эмпирический эффект, но также слабые научные доказательства [56]. В обзоре, посвященном вопросам лечения ОФБ, отмечено, что ряд используемых препаратов, прежде всего нестероидные противовоспалительные препараты (НПВП), могут вызывать целый ряд побочных эффектов, которые как осложняют стоматологическое лечение, так и негативно влияют на сопутствующую коморбидную патологию [57].…”
Section: лечение орофациальной болиunclassified
“…[20] Overall, the available data are still insufficient to prove that dietary supplements may help prevent and/or treat COVID-19. [21–24]…”
Section: Introductionmentioning
confidence: 99%
“…[20] Overall, the available data are still insufficient to prove that dietary supplements may help prevent and/or treat COVID-19. [21][22][23][24] Although their effects are unproven, various DS/HF are recommended to prevent and treat COVID-19 through social media and conventional media platforms. [25] The vast majority of news during the COVID-19 pandemic offered preventive and protective methods against COVID-19, most of which were related to HF, vitamins, and minerals without offering any scientific evidence.…”
Section: Introductionmentioning
confidence: 99%